F2RL3 methylation in blood DNA is a strong predictor of mortality - Zhang, Yan; Yang, Rongxi; Burwinkel, Barbara; Breitling, Lutz Philipp; Holleczek, Bernd; Schöttker, Ben; Brenner, Hermann (International journal of epidemiology, 2014)
Abstract. Background: Smoking is a major cause of morbidity and mortality. Smoking-related epigenetic biomarkers may open new avenues to better quantify the ad
Advance access publication date: 7 February 2014
Gesehen am 15.09.2020